1994
DOI: 10.1055/s-2007-1021026
|View full text |Cite
|
Sign up to set email alerts
|

The Validity and Accuracy of Blood Lactate Measurements for Prediction of Maximal Endurance Running Capacity

Abstract: The effect of using different blood lactate sampling sites in combination with different exercise test designs on the validity and accuracy for prediction of maximal endurance running velocity was investigated. Ten aerobically all-round trained firemen and nine aerobically endurance trained long-distance runners performed six differently designed treadmill running blood lactate accumulation tests. Each test consisted of five consecutive running periods on a treadmill of either 4, 6 or 8 min duration, with a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Other authors investigated the influence of step duration on the ªOnset of Blood Lactate Accumulationº [26] and could not prove any influence [32]. On the other hand Foxdal et al [9] reported the most reliable results in determining a physiological threshold when using long step durations connected with low increments because of the better applicability of the absolute lactate concentrations from the step test to the endurance training (independent of the reference to the maximal lactate steady state). In order to evalu- ate the quality of the different test procedures, the difficulties concerning the intensity recommendations on the basis of fixed lactate values have to be considered.…”
Section: Preliminary Exercisementioning
confidence: 99%
“…Other authors investigated the influence of step duration on the ªOnset of Blood Lactate Accumulationº [26] and could not prove any influence [32]. On the other hand Foxdal et al [9] reported the most reliable results in determining a physiological threshold when using long step durations connected with low increments because of the better applicability of the absolute lactate concentrations from the step test to the endurance training (independent of the reference to the maximal lactate steady state). In order to evalu- ate the quality of the different test procedures, the difficulties concerning the intensity recommendations on the basis of fixed lactate values have to be considered.…”
Section: Preliminary Exercisementioning
confidence: 99%
“…Incremental intensity blood lactate exercise tests are accepted as valid and reliable estimators of endurance performance [1, 2, 7,11,12,18,19,28]. Moreover, lactate parameters derived from these tests are used to assign training intensities [6, 9,14 ± 16, 26, 32, 35].…”
Section: Introductionmentioning
confidence: 99%
“…A field-based and submaximal test would be more advantageous for soccer players in terms of applicability and acceptability. Such a test, however, is likely to elicit a different HR-[La] relationship [3,8,30], which would not support an interchangeable use of the present method. Although the sample size was not limited, more training and testing cases from heterogeneous groups are needed in the future for better generalizability.…”
Section: Discussionmentioning
confidence: 94%